2004
DOI: 10.1093/chemse/bjh040
|View full text |Cite
|
Sign up to set email alerts
|

A Longitudinal Descriptive Study of Self-reported Abnormal Smell and Taste Perception in Pregnant Women

Abstract: Self-reported abnormal sensitivity, qualitative distortions and phantom sensations with respect to smell and taste was assessed with a longitudinal design, based on questions referring to gestational weeks 13-16 and 31-34 of pregnancy in comparison with 9-12 weeks post partum and with non-pregnant women with corresponding time durations and intervals. The results show that abnormal smell and/or taste perception was reported by 76% of the pregnant women, typically believed to be caused by their pregnancy. Incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
64
2
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 86 publications
(69 citation statements)
references
References 20 publications
2
64
2
1
Order By: Relevance
“…Metallic sensations have also been reported as a side effect of drugs (27) and throughout pregnancy (28). Moreover, metallic taste might be elicited by oral yeast infections (29), burning mouth syndrome (30), damage by stapedectomy or anesthesia of the chorda tympani (31,32), artificial sweeteners (33), and dental amalgam fillings (34).…”
Section: Discussionmentioning
confidence: 99%
“…Metallic sensations have also been reported as a side effect of drugs (27) and throughout pregnancy (28). Moreover, metallic taste might be elicited by oral yeast infections (29), burning mouth syndrome (30), damage by stapedectomy or anesthesia of the chorda tympani (31,32), artificial sweeteners (33), and dental amalgam fillings (34).…”
Section: Discussionmentioning
confidence: 99%
“…and have been linked to specific taste aversions and taste preferences in pregnant women (Nordin et al 2004), but have not been found to be associated with nausea during early pregnancy (Hummel et al 2002). The mechanisms behind these phenomena, thus, are incompletely understood.…”
Section: Discussionmentioning
confidence: 99%
“…The smell anomalies were found less common at late pregnancy and nearly absent during the postpartum stage. [22] 90% of pregnant women stated that some odors were sensed less pleasing. These and earlier results may reveal that the pregnancy's effect on olfaction is minor and varying.…”
Section: Nasal Symptoms In Pregnancymentioning
confidence: 99%